The soft vengeance of a freedom fighter - Sachs, Albie, 1935- (University of California Press, 2014)
On April 7, 1988, Albie Sachs, an activist South African lawyer and a leading member of the ANC, was car-bombed in Maputo, the capital of Mozambique, by agents of South Africa's security forces. His right arm was blown off, and he lost sight in one eye. This intimate and moving account of his recovery traces the gradual recuperation of his broken body and his triumphant reentry into the world, where his dream of soft vengeance was realized with the achievement of democracy in South Africa. This book captures the spirit of a remarkable man: his enormous optimism, his commitment to social justic.